Changes in Serum Calcitonin Concentrations, Incidence of Medullary Thyroid Carcinoma, and Impact of Routine Calcitonin Concentration Monitoring in the EXenatide Study of Cardiovascular Event Lowering (EXSCEL) - Bethel, M. Angelyn (Diabetes Care, 2019)
OBJECTIVE: Increases in serum calcitonin, a tumor marker for medullary thyroid carcinoma (MTC), have been associated with glucagon-like peptide 1 receptor agonist use in some preclinical studies. We report calcitonin changes in exenatide-treated and placebo-administered participants and MTC incidence in the EXenatide Study of Cardiovascular Event Lowering (EXSCEL) and consider the impact of within-trial calcitonin monitoring. RESEARCH DESIGN AND METHODS: EXSCEL participants were randomized 1:1 to once-weekly exenatide 2 mg or placebo. Serum calcitonin was measured at baseline (with trial medication discontinued if >40 ng/L) and annually thereafter (with trial medication discontinued if ≥50 ng/L). Median calcitonin concentrations were calculated at each time point, and thyroid malignancies were collected prospectively. Data regarding follow-up after an elevated calcitonin were collected retrospectively. RESULTS: At baseline, 52 (30 exenatide and 22 placebo) participants had calcitonin >40 ng/L, and during follow-up an additional 23 participants (15 exenatide and 8 placebo) had calcitonin ≥50 ng/L in the intention-to-treat population. Median calcitonin concentrations were similar between treatment groups at baseline with no increase over time. Confirmed MTC occurred in three participants (2 exenatide and 1 placebo), all of whom had significantly elevated baseline calcitonin values (413, 422, and 655 ng/L). CONCLUSIONS: During a median 3.2 years’ follow-up, no change in serum calcitonin was seen with exenatide therapy. The three confirmed cases of MTC all occurred in participants with markedly elevated baseline calcitonin levels, measured prior to trial medication administration. Regular calcitonin monitoring identified no additional cases of MTC, suggesting no benefit of routine calcitonin monitoring during exenatide treatment.